The other side of now : a novel - Harbison, Paige (St. Martin's Press, 2025)
A hilarious and heartfelt novel about how loves and lives are never truly lost, for fans of Rebecca Serle and Taylor Jenkins Reid. With a leading role on a hit TV show and a relationship with Hollywood's latest heartthrob, Meg Bryan appears to have everything she ever wanted. But underneath, her happiness is as fake as her stage name, Lana Lord. Following a tiny nervous breakdown at her thirtieth birthday party, she books an impromptu trip to Ireland. Specifically, to the village where she and her best friend Aimee always dreamt of moving. When Meg arrives, the people in town don't just recognize her, they seem to know her. She quickly--reluctantly--realizes she has somehow slipped into an alternate reality. One where she did move to Ireland as a teenager, one where she never got famous, and--most shocking of all--one where Aimee is alive and well. She just wants nothing to do with Meg. Despite her bewilderment, Meg is clear-eyed about one thing: this is a once-in-two-lifetimes chance to reconnect with her friend and repair what she broke . . . or else risk losing Aimee all over again.